Polyphosphate accumulation in microalgae and cyanobacteria: recent advances and opportunities for phosphorus upcycling. - Plouviez M; Brown N (Elsevier B.V., 2024)
Phosphorus (P) must continuously be added to soils as it is lost in the food chain and via leaching. Unfortunately, the mining and import of P to produce fertiliser is unsustainable and costly. Potential solutions to the global issues of P rock depletion and pollution lie in microalgae and cyanobacteria. With an ability to intracellularly store P as polyphosphates, microalgae and cyanobacteria could provide the basis for removing P from water streams, thereby mitigating eutrophication, and even enabling P recovery as P-rich biomass. Metabolic engineering or changes in growing conditions have been demonstrated to improve P removal and recovery by triggering polyphosphates synthesis in the laboratory. This now needs to be replicated at full scale.